Awareness, Attitudes, and Practices of the Exercise Buddy System Among Overweight and Obese Individuals in India: A Cross‐Sectional Study - Patel, Khyati; Gadhavi, Bhavana; Bhatt, Geeta; Mehendale, Priti (National Journal of Community Medicine, 2025)
Background: Overweight and obesity are growing health problems in India due to city living and lifestyle changes. Regular exercise helps prevent chronic diseases, but many people struggle to stick with it. The exercise buddy system, where two people exercise together, may improve motivation and consistency. However, few studies explore how well-known this method is. This study examined awareness, opinions, and use of the buddy system among overweight and obese adults in India. Methods: We conducted a study with 80 adults (aged 18–60 years; BMI ≥ 24.9 kg/m²). Participants were recruited through online surveys on social media and in-person interviews at a hospital clinic. A questionnaire collected data on demographics, exercise habits, and awareness and opinions of the buddy system using an eight-item scale. We ensured data quality with strict checks. Data were analyzed using SPSS v21 with descriptive, chi-square, and regression analyses. Results: Participants’ average age was 45 years; 56.3% were women. Most (92.5%) exercised regularly, but 72.5% did so alone. Only 11.3% knew about the buddy system before the study. After learning about it, most had positive views (Cronbach’s α = 0.82). Higher positive opinions increased willingness to try the buddy system by 35% (OR = 1.35, p = 0.004). Conclusion: While baseline awareness of the exercise buddy system is low among overweight and obese individuals in India, the generally positive attitudes indicate significant potential for its integration into physical activity interventions. Future research should focus on educational strategies to enhance awareness and overcome barriers to adoption.